2012
DOI: 10.4067/s0034-98872012001000003
|View full text |Cite
|
Sign up to set email alerts
|

El cambio del perfil epidemiológico de la mortalidad materna en Chile dificultará el cumplimiento del 5° objetivo del Milenio

Abstract: The change in the epidemiological profile of maternal mortality in Chile will hinder the fulfillment of the (r = 0.656, p = 0.035). Abortion associated mortality had a significant downward trend (r = -0.712, p = 0.023). The group of women 40 years and older significantly increased its birth rate (r = 0.930, p < 0.001), this group showed the highest maternal mortality, especially in association with concurrent diseases. Conclusions: The increased birth rate occurring in women over 40 years old and its larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 20 publications
0
13
0
10
Order By: Relevance
“…In Latin America, Souza et al’s study [31] found that 16 % of adolescent deaths in Brazil were caused by haemorrhage, whereas de Sequeira et al’s (1986) study, also in Brazil [32], which had a larger sample size estimated this to be 8 %. Studies in Peru [33] and Chile [19] attributed 13 and 8 % respectively to this cause. Again, this is markedly lower than the figure assigned by Say et al [10] for this region.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Latin America, Souza et al’s study [31] found that 16 % of adolescent deaths in Brazil were caused by haemorrhage, whereas de Sequeira et al’s (1986) study, also in Brazil [32], which had a larger sample size estimated this to be 8 %. Studies in Peru [33] and Chile [19] attributed 13 and 8 % respectively to this cause. Again, this is markedly lower than the figure assigned by Say et al [10] for this region.…”
Section: Resultsmentioning
confidence: 99%
“…Where estimates were also available from other age groups, no discernible patterns were evident: whilst in some studies the estimates for adolescents were somewhat higher [23, 24], in others they were lower [29] and in some they were very similar [18, 26, 30]. Three of the Latin American studies had very similar estimates of 16 or 17 %, whereas the fourth was much lower at 3 % [19]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Existe concordancia en que por primera vez en los últimos cincuenta años, la situación materna está estancada, sin variaciones significativas en los últimos diez años (11). Esta situación es altamente inestable y por lo tanto es deseable que se implementen a corto plazo nuevos programas específicos orientados a enfrentar esta nueva situación epidemiológica.…”
Section: Proposiciones De Consensounclassified
“…From that time Chile has experienced a steady decline, reaching a rate of 12 deaths per 100,000 live births in 2010. 3 Continuous improvement in universal access to quality services in reproductive health, incorporating a national program for the control of fertility and the promotion of skilled birth attendance are part of the foundation responsible for the national demographic change in the last 50years. 4 However, in recent years the indicator has remained stable: 22 projected deaths per 100,000 live births by the year 2015 rate where comorbidities of chronic non-communicable diseases is and will be the main problem.…”
Section: Introductionmentioning
confidence: 99%